THE EFFECTIVENESS OF THE BATAM CITY GOVERNMENTS ROLE IN REDUCING THE INCIDENCE OF EARLY MARRIAGE - Rahmadani, Aini; Dewi Seroja, Triana; Tan, Winsherly (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Early marriage remains a significant social issue in Indonesia, particularly in Batam City, despite legal regulations setting the minimum marriage age at 19. This study evaluates the effectiveness of the Batam City Government's role in reducing early marriage rates, identifies obstacles, and proposes solutions. Using an empirical legal approach, data were collected through observations at the UPTD for Women and Children Protection (PPA) and the Population and Civil Registration Office, along with secondary sources such as legal documents and reports. Findings reveal that economic pressures, cultural norms, lack of education, and limited reproductive health awareness contribute to persistent early marriages. From 2019 to 2024, Batam recorded 119 early marriage cases, with economic hardship and premarital pregnancies as primary drivers. The government faces challenges, including weak community adherence to legal standards, insufficient coordination among agencies, and resistance from traditional leaders. Proposed solutions include intensifying public education campaigns, integrating reproductive health into school curricula, providing economic support for low-income families, and enhancing parental guidance programs. Strengthening inter-agency collaboration and conducting regular program evaluations are also critical. This study highlights the need for a comprehensive, multi-stakeholder approach to effectively reduce early marriage rates, ensuring better protection of children's rights and long-term societal well-being.